The Relationship of Quranic Qiraat and Sunnah - Mohamed Fathy, Mohamed Abdelgelil; Ahmad Fauzi, Hassan; Azizul, Hassan (2020)
Quranic Mutawatir (Authentic) Qiraat (readings, recitations) and Sunnah (prophetic tradition) were both delivered by prophet Mohammed peace be upon him. This paper was conducted to show that the prophetic tradition is the source of Mutawatir Quranic Qira’at to correct the misbelief that Qiraat may have been originated from other sources. Thus, the purpose of this paper is to show the relationship between Quranic Qira’at and prophetic tradition on the one hand and the extent of this relationship on the other. The research takes an analytical approach by tracking the texts whose interpretation leads to this judgement. The research shows that the relationship between Quranic Qira’at and prophetic traditions is perfectly clear since they were both delivered by prophet Mohammed peace be upon him.